Pengaruh Kecerdasan Emosional dan Minat Belajar terhadap Prestasi Belajar Al-Qur'an Hadis - Zhulfatin Zahro'; Mulyoto (Program Pascasarjana UNU Surakarta, 2022)
This study aims to determine: 1) Emotional intelligence of class VIII MTsN Filial Kartasura students for the 2019/2020 Academic Year. 2) Interest in learning of class VIII MTsN Filial Kartasura students for the 2019/2020 Academic Year. 3) The influence of emotional intelligence and interest in learning on the learning achievement of the Qur'an Hadith for class VIII MTsN Filial Kartasura students for the 2019/2020 Academic Year. This research is quantitative. The study was conducted at MTsN Filial Kartasura to determine the influence of emotional intelligence variables and learning interest variables on the variables of learning achievement of the Qur'an Hadith for class VIII students. The study population was 60 students using random sampling. Data analysis was carried out using correlation and multiple linear regression analysis. The results of this study show that: 1) The emotional intelligence of MTsN Filial Kartasura students is quite good but has no effect on the learning achievement of the Qur'an Hadith, 2) The interest in learning the Qur'an Hadith of MTsN Filial Kartasura students has a positive effect on the learning achievement of the Qur'an Hadith, 3) There is a positive influence between emotional intelligence and interest in learning on the learning achievement of the Qur'an Hadith of MTsN Filial Kartasura students. From the results of this study, it can be concluded that emotional intelligence and interest in learning affect the learning achievement of the Qur'an Hadith for class VIII MTsN Filial Kartasura Sukoharjo students.